Integration of Local Wisdom in Sustainable Ecotourism Management from the Perspective of Indigenous Communities - Lasaiba, Mohammad Amin (JENDELA PENGETAHUAN, 2022)
With time, the terminology of ecotourism continues to evolve. This study aims to explore the role of local wisdom in the sustainable management of ecotourism from the perspective of indigenous communities in Indonesia. This research focuses on how traditional knowledge and practices can be integrated into ecotourism management to support environmental sustainability, enhance the economic welfare of local communities, and strengthen cultural identity. The research method used is a literature review, examining relevant journals and literature from the past five years. The findings show that the active involvement of indigenous communities in ecotourism management, as seen in Komodo National Park, the Subak system in Bali, and indigenous communities in North Sulawesi, can yield significant benefits. Indigenous community participation increases conservation awareness, community participation, and fair distribution of economic benefits. However, challenges such as lack of policy support and conflicts of interest must be addressed. This study recommends developing policies that recognize and value local wisdom, capacity building for indigenous communities through training and education, and implementing participatory approaches at every stage of ecotourism project planning and execution